Improving wear resistance of functional surfaces using the machine hammer peening technique. (March 2014) - Rodríguez Ripoll, M.; Heindl, F.; Lechner, C.; Habersohn, C.; Jech, M.; Bleicher, F.
<x content-type="archive" xml:space="preserve">Abstract</x> Machine hammer peening (MHP) is a novel surface treatment technology, which creates smoother surfaces with a local hardness increase and compressive residual stresses well below the surface. By these means, properties of functional surfaces can be enhanced, which opens a broad range of potential applications, especially for surfaces undergoing tribological contact. In the present work, two commercially available steels are processed using the MHP technique. Additionally, the technique is applied as a tool for embedding hard particles into the surfaces of samples. The tribological performance of the MHP processed samples is investigated under reciprocating sliding conditions using a ball-on-flat configuration. The wear resistance of the samples is analysed using optical and white light confocal microscopy methods. The results show a significant increase in terms of wear resistance for MHP samples with embedded hard particles.